Alcohol in minors - a harmless fad or a serious problem? - Gabriela Świątek; Rafał Tkaczyk; Weronika Sosnowska; Maria Tomkiewicz; Kalina Taracha; Jakub Tomczyk; Maciej Tomkiewicz; Aleksandra Brzozowska; Magdalena Śwital; Michał Tokarski (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Alcohol has been known for centuries. In recent years, awareness of the effects of its consumption has been growing and acceptance of the drink has been declining. Despite this, there is an increase in young alcohol consumption and a decrease in the age of alcohol initiation. In this work, the problem of alcohol consumption by minors will be reviewed based on the evaluation of hospitalizations in the Clinical Department of Toxicology and Cardiology of the Stefan Cardinal Wyszynski Regional Hospital in Lublin in 2022. The aim of the study is to draw attention to this important, although often downplayed, problem.